New petrographic, geochemical and geochronological data for the Reguengos de Monsaraz pluton (Ossa Morena Zone, SW Iberian Massif, Portugal) - Antunes, A. (2012)
The Reguengos de Monsaraz pluton is a late to post-tectonic Variscan intrusion occurring in the Ossa Morena Zone (Iberian Variscan Chain). The dominant lithological types are tonalites and granodiorites, but the internal area of the massif is composed of gabbro-dioritic rocks. Field evidence shows that the intrusion is heterogeneous at mesoscopic scale suggesting that the emplacement of mafic and felsic magmas was contemporaneous. Petrographic and geochemical studies reveal that the different lithologic types define a continuous sequence with compositions varying from metaluminous to slightly peraluminous and a typical calc-alkaline signature. In Harker variation diagrams, it is possible to observe systematic rectilinear correlations pointing to the involvement of magma mingling/mixing processes in the petrogenesis of this sequence. Rb-Sr isotopic data, using a mineral-mineral pair from a granodiorite sample, yielded an age of 298 Ma, interpreted as a cooling age after igneous crystallization.